"Magnitude of community-based health insurance utilization and associated factors in Bassona Worena District, North Shoa Zone, Ethiopia: a community-based cross-sectional study" - Tomas Getahun; Lakech Teklesilassie; Mizan Habtemichael; Yonas Abebe; Helen Getahun (BMC, 2022)
Abstract Introduction The health insurance system has been proven to offer effective and efficient health care for the community, particularly community-based health insurance is expected to ensure health care access for people with low economic status and vulnerable groups. Despite the significance of evidence-based systems and implementation, there is a limited report about the magnitude of CBHI utilization. Therefore, this study was done to assess factors associated with community-based health insurance utilization in Basona Worena District, North Shewa Zone, Ethiopia. Method A community-based cross-sectional study was employed. We have included 530 households from 6 randomly selected kebeles. The data was entered using Epi-Data V 3.1 and exported to SPSS version 20.0 for statistical analysis. Bi-variable and multivariable logistic regression analyses were computed to determine factors associated with community-based health insurance utilization. Result The study finding shows that 58.6% of the respondents were members of community-based health insurance. Respondents who had primary and secondary education levels were 2 times more likely to be members than those who had no formal education. As compared to those who had awareness, respondents who had no awareness about CBHI were 0.27 times less likely to be insured. Respondents who did not experience illness were 0.27 times less likely to be members than respondents who experienced illness. Conclusion Educational status, awareness about CBHI, perception of CBHI scheme and illness experience of family influence CBHI utilization. There is a need to strengthen awareness creation to improve the CBHI utilization.